Optimization of Financing Role of Islamic Banks Development of Micro Small and Medium Enterprises (MSME) In Bandar Lampung - A. Zuliyansyah (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2019)
The development potential of MSME in Indonesia can not be separated from the support of banks in lending to MSMEs. MSME loans are loans to borrowers of micro, small and medium enterprises that meet the definition and criteria of micro, small and medium enterprises as stipulated in Law No. 20 of 2008 on MSMEs. Under the bill, MSMEs are productive businesses that meet the criteria of business within certain constraints net worth and annual sales revenue. This study aims to look at how is the implementation of Islamic bank financing for the development of MSMEs in the city of Bandar Lampung. Are the problems faced by Islamic banks in financing to MSMEs in Bandar Lampung and how efforts can be taken to optimize the Syariahagainst Bank financing the development of MSMEs in the city of Bandar Lampung. From the results of field research on MSMEs respondents conclusion that the financing of consumption used for productive activities can reach ± 40% of the total MSME financing consumption. The number is obtained by adding the percentage of the use of pure MSME consumer financing for business activities (28%), for personal purposes which turned out to be used for business activities (8.7%) and the use of financing for personal use and business activities or the use of